Masculinities in Doraemon: A Critical Discourse Analysis - Zhouyan Wu; Zhaoxun Song (Journalism and Media)
This study conducts a Critical Discourse Analysis of the masculinities of male characters in Doraemon, a famous Japanese manga series. It explores the masculinities in Doraemon from three perspectives by utilising the following Critical Discourse Analysis framework: text, process and society. Five male characters in Doraemon were selected as the main research objects. Firstly, the text analysis of the male characters in terms of their appearances, characteristics, behaviours and values reveals major masculine traits such as the maintenance of patriarchy, the pursuit and yearning for fame and fortune, competition and aggression. Analysing these masculinities can help remind audiences and consumers to be cautious about works that seemingly do not convey gender stereotypes to viewers. The process analysis identifies corresponding masculinities of the creator of Doraemon through his life experiences. Innovative spirit led him to create characters and manga that could both reflect and confront social reality and promote new gender concepts and ideas that were different from the mainstream at the time. The social analysis of Doraemon attributes the masculinities in the manga to Japanese culture, which has been deeply influenced by the culture of the salaryman, Confucianism, androcentrism and Bushido. For audiences in Japan, anime is a way of spreading and consolidating traditional Japanese cultural ideas, at the same time provoking reflection on whether these inherent gender roles are reasonable and should be perpetuated in the contemporary era. For audiences outside of Japan, this manga and cartoon is equivalent to a typical case of the export and recreation of Japanese culture to the world. This study conveys gender equality values, especially in children’s TV programmes.